Purple crayons : the art of drawing a life - Ellenhorn, Ross D. (Harper Wave, an imprint of HarperCollins Publishers, 2022)
"A rereading of children's book Harold and the Purple Crayon by Crockett Johnson, in which psychologist Ross Ellenhorn celebrates our inherent "sacred originality," and establishes a new framework for self-reliance"--